Classical Greek theatre : new views of an old subject - Ashby, Clifford (Studies in theatre history and culture., 1999)
Many dogmas regarding Greek theatre were established by researchers who lacked experience in the mounting of theatrical productions. In his wide-ranging and provocative study, Clifford Ashby, a theatre historian trained in the practical processes of play production as well as the methods of historical research, takes advantage of his understanding of technical elements to approach his ancient subject from a new perspective. In doing so he challenges many long-held views. Archaeological and written sources relating to Greek classical theatre are diverse, scattered, and disconnected. Ashby.